Nutrient consumption of green microalgae, Chlorella sp. during the bioremediation of shrimp aquaculture wastewater - Mohd Nasir, Nurfarahana; Jusoh, Ahmad; Harun, Razif; Nik Ibrahim, Nik Nor Liyana; Rasit, Nazaitulshila; Wan Abdul Karim Ghani, Wan Azlina; Kurniawan, Setyo Budi (Elsevier, 2023)
Aquaculture products are among the biggest contributor to food supplies to meet the global food demands of the growing population over these past few years. For aquaculture to continue developing, an effective wastewater treatment is required to lessen the environmental effects. This study examined the potential of Chlorella sp. to reduce nutrients in shrimp aquaculture wastewater and correlate with the growth kinetics of the algae during the bioremediation process. Six different Chlorella sp. inoculation dosages ranging from 0 to 60 % (v/v) were used in this study. Marine water wastewater (MW) and Freshwater wastewater (FW) where the two types of shrimp wastewater were employed. Results indicated that the 30 % (v/v) and 40 % (v/v) were the optimum dosage for MW and FW. During the treatment, microalgae cell density increased more than tenfold compared to the initial value. Moreover, batch culture resulted in the specific growth rate concentration of 0.18 k day− 1 and 0.15 k day− 1 , respectively. Those dosage also resulting the highest removal efficiencies with removal of ammonia, nitrite and orthophosphate of 96.77 %, 82.07 %, 75.96 % and 90.10 %, 87.09 %, 95.60 %, respectively. The application of FTIR spectroscopy was employed in this study to analyze the functional group in the microalgae biomass. The results of the scanning electron microscopy (SEM) and Energy Dispersive Spectroscopy Analysis (EDS) also included to further illustrate how microalgae biomass was affected by the treatment in this study. Therefore, the research from this study could be used in design novel microalgae treatments that offer a thorough and environmentally beneficial method of treating shrimp aquaculture wastewater.